A review of four case studies assessing the potential for hydrogen penetration of the future energy system. (8th March 2019) - Chapman, Andrew; Itaoka, Kenshi; Hirose, Katsuhiko; Davidson, F. Todd; Nagasawa, Kazunori; Lloyd, Alan C.; Webber, Michael E.; Kurban, Zeynep; Managi, Shunsuke; Tamaki, Tetsuya; Lewis, Michael C.; Hebner, Robert E.; et al.
Abstract: Hydrogen as an energy carrier allows the decarbonization of transport, industry, and space heating as well as storage for intermittent renewable energy. The objective of this paper is to assess the future engineering potential for hydrogen and provide insight to areas of research to help lower economic barriers for hydrogen adoption. This assessment was accomplished by creating top-level system models based on energy requirements for end-use services. Those models were used to investigate four case studies that provide a global view augmented with specific national examples. The first case study assesses the potential penetration of hydrogen using a global energy system model. The second applies the dynamic integrated climate–ecosystem–economics model to derive an estimate of the impact of the diffusion of hydrogen as an energy carrier. The third determines the required growth in renewable power and water usage to power transportation in the United States (US) with hydrogen. The fourth assesses the use of hydrogen for heating in the United Kingdom (UK). In all cases, there appeared to be significant potential for hydrogen adoption and net energetic benefit. Globally, hydrogen has the potential to account for approximately 3% of energy consumption by 2050. In the US, using hydrogen for on-road transportation could enable a reduction in rejected energy of nearly 10%. Also, hydrogen might provide the least cost alternative to decarbonizing space heating in the UK. The research highlights a challenge raised by widespread abandonment of nuclear power. It is currently unclear what the removal of nuclear would do to the cost of energy as nations attempt to limit global greenhouse gas emissions. Nuclear power has also been proposed as a source for large scale production of hydrogen. Finally, this analysis shows that with today's technological maturity making the transition to a hydrogen economy would incur significant costs. Highlights: Explores four case studies of the societal penetration of hydrogen. Identifies the decarbonizing benefits of hydrogen in transport and heating. Global model identifies nation specific opportunities for hydrogen penetration. Cost remains a significant challenge to the ushering in of the hydrogen economy. Cost reductions in hydrogen production, storage and transmission are necessary.